Zróżnicowanie przestrzenne i dynamika rozwoju gospodarstw ekologicznych w Polsce - Brodziński, Zbigniew (Spatial Differentiation and Dynamics of Development of Ecological Farms in Poland, 2006)
The study presents the spatial differentiation of ecological farms in Poland, the changes in the farms' area structure and the trends in the land use. The numerical data on the ecological cultivation farms have been taken from the GUS (Central Statistical Office of Poland) publications for the years 2000 and 2004. The selected time bracket allows indication of the key development-related trends in the relevant group of farms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 122-128